National Trends in Outpatient Surgical Treatment of Degenerative Cervical Spine Disease - Baird, Evan O. (Georg Thieme Verlag KG, 2014)
Study Design Retrospective population-based observational study. Objective To assess the growth of cervical spine surgery performed in an outpatient setting. Methods A retrospective study was conducted using the United States Healthcare Cost and Utilization Project's State Inpatient and Ambulatory Surgery Databases for California, New York, Florida, and Maryland from 2005 to 2009. Current Procedural Terminology, fourth revision (CPT-4) and International Classification of Diseases, ninth revision Clinical Modification (ICD-9-CM) codes were used to identify operations for degenerative cervical spine diseases in adults (age > 20 years). Disposition and complication rates were examined. Results There was an increase in cervical spine surgeries performed in an ambulatory setting during the study period. Anterior cervical diskectomy and fusion accounted for 68% of outpatient procedures; posterior decompression made up 21%. Younger patients predominantly underwent anterior fusion procedures, and patients in the eighth and ninth decades of life had more posterior decompressions. Charlson comorbidity index and complication rates were substantially lower for ambulatory cases when compared with inpatients. The majority (>99%) of patients were discharged home following ambulatory surgery. Conclusions Recently, the number of cervical spine surgeries has increased in general, and more of these procedures are being performed in an ambulatory setting. The majority (>99%) of patients are discharged home but the nature of analyzing administrative data limits accurate assessment of postoperative complications and thus patient safety. This increase in outpatient cervical spine surgery necessitates further discussion of its safety.